Toán 9 Giải phương trình:

phuclam5905

Học sinh
Thành viên
9 Tháng mười 2020
93
67
21
20
Thanh Hóa
THPT TX5
ĐK x>0
x2+12+3=x2+5+2xx2+124=x2+53+2x4x24x2+12+4x24x2+5+32(x2)=0(x2)(x+2x2+12+4x+2x2+5+32)=0\sqrt{x^{2}+12}+3=\sqrt{x^{2}+5}+2x \Leftrightarrow \sqrt{x^{2}+12}-4=\sqrt{x^{2}+5}-3+2x-4 \Leftrightarrow \frac{x^{2}-4}{\sqrt{x^{2}+12}+4}-\frac{x^{2}-4}{\sqrt{x^{2}+5}+3}-2(x-2)=0 \Leftrightarrow (x-2)(\frac{x+2}{\sqrt{x^{2}+12}+4}-\frac{x+2}{\sqrt{x^{2}+5}+3}-2)=0
x=2\Rightarrow x=2 .....
 
  • Like
Reactions: Ejio

Bách Lý Thiên Song

Học sinh chăm học
Thành viên
22 Tháng chín 2020
889
680
111
ĐK x>0
x2+12+3=x2+5+2xx2+124=x2+53+2x4x24x2+12+4x24x2+5+32(x2)=0(x2)(x+2x2+12+4x+2x2+5+32)=0\sqrt{x^{2}+12}+3=\sqrt{x^{2}+5}+2x \Leftrightarrow \sqrt{x^{2}+12}-4=\sqrt{x^{2}+5}-3+2x-4 \Leftrightarrow \frac{x^{2}-4}{\sqrt{x^{2}+12}+4}-\frac{x^{2}-4}{\sqrt{x^{2}+5}+3}-2(x-2)=0 \Leftrightarrow (x-2)(\frac{x+2}{\sqrt{x^{2}+12}+4}-\frac{x+2}{\sqrt{x^{2}+5}+3}-2)=0
x=2\Rightarrow x=2 .....
mình nghĩ không cần đk đâu
 
Top Bottom